Injunctions and Collective Redress: European Mission and Vision - Ragone, Alvaro Pérez (2021)
This is a descriptive-evolutive, dogmatic and comparative study on the collective processes of the European Union (EU). On November 25th, 2020, the Union adopted one of its most awaited legal instruments: the firstlegislation, that is supposed to create a European collective action mechanism for monetary relief. According to Directive 2020/1828 on representative actions for the protection of the collective interests of consumers, and repealing Directive 2009/22/EC, member States have to adopt the transposing measures by December 25th, 2021, and give effect to them on and apply them to representative actions that are brought on or after June 25th, 2023. The European movement for collective litigation started approximately three decades ago. It earned official European recognition in competition law in 2005, owing to the European Commission’s Green Paper on Damages Actions for Breach of the EC Antitrust Rules, followed by the White Paper of the sametitle in 2008. From 2013 to the emission of the recent 2020 directive, the particularity of community collective redress and inhibitory guardianship has proven to be holistic, unlike the US class action model.This paper analyzes the three pillars of the European vision on collective redress seeking, namely: a) the extrajudicial alternative dispute resolution mechanisms, b) the regulatory and public policy mechanisms, and c) the collective processes or litigation. The interplay of these three pillars makes the European Union’s view on the matter singular as it proposes a system of incentives, prudence and safeguards.